Beyond Necessity: How Generation Z in Poland Engages with Informal Markets for Sustainable Consumption - Małecka, Agnieszka; Pfajfar, Gregor (Wychodząc poza konieczność: jak pokolenie Z w Polsce angażuje się w nieformalne rynki zrównoważonej konsumpcji, 2025)
Aim: This study focused on the interdependence of the informal economy and sustainable consumer behaviour. By using cluster analysis, it challenges traditional views that categorise the informal economy as marginal and economically backward. Methodology: A survey was used to collect the data from a group of respondents from Poland, representing generation Z (n = 115). Results: The research results made it possible to distinguish between two groups: one that actively chooses informal markets based on values, such as concern for the environment, social equality and identification with the global community, and another one that leans towards more traditional market approaches. The paper highlights that participation in the informal market involves a value-based choice influenced by ethical, environmental and ideological considerations, among others. Implications and recommendations: The findings offer valuable implications for policymakers and businesses, stressing the need for adaptive action that is in line with emerging consumer priorities and the changing role of the informal economy in sustainable development. Originality/value: This study links economic behaviour with psychological constructs. Previous research in this area focused on informal market participation to a very limited extent, mainly among marginalised groups (e.g. low-income populations). In turn, consumers with other characteristics, such as greater concern for the environment and a perceived need for equality, also engage in the informal economy, suggesting that ethical and sustainability considerations may guide informal market choices.
Financial Sciences. Nauki o Finansach, 2025, vol. 30, no. 1, s. 14-23
Keywords: informal economy; consumer behaviour; sustainability; equality; consumer resistance; gospodarka nieformalna; zachowanie konsumenta; zrównoważony rozwój; równość; opór konsumenta